Defenders of Order or Guardians of Human Rights? - Schwendinger, Herman (Social justice, 2013)
The article discusses a review of some complex issues involved in a 30 year-old controversy on the definition of crime. Topics discussed include 2 developments that stimulated the issue raised during the Great Depression such as the rapid growth of a corporate liberal empiricism and the socially critical interest in white collar crime, preferred defining criteria by the scholars involved in the 30 year old controversy and suggestion that the definition of crime should openly face moral issues.